2019
DOI: 10.1373/jalm.2019.029801
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Conversion Assays Diagnostic for Neurodegenerative Proteinopathies

Abstract: Background In vitro conversion assays, including real-time quaking-induced conversion (RT-QuIC) and protein misfolding cyclic amplification (PMCA) techniques, were first developed to study the conversion process of the prion protein to its misfolded, disease-associated conformation. The intrinsic property of prion proteins to propagate their misfolded structure was later exploited to detect subfemtogram quantities of the misfolded protein present in tissues and fluids from humans and animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…RT-QuIC and related methods are becoming tractable approaches for end-point diagnostic detection due to their high sensitivity to detect α-syn aggregates. [36,[39][40][41] However, these tools lack the ability to resolve features that may only be revealed at a single molecule level. The fluorescence approach described here is conceptually equivalent to RT-QuIC since it relies on ThT staining with an isothermal amplification step.…”
Section: Discussionmentioning
confidence: 99%
“…RT-QuIC and related methods are becoming tractable approaches for end-point diagnostic detection due to their high sensitivity to detect α-syn aggregates. [36,[39][40][41] However, these tools lack the ability to resolve features that may only be revealed at a single molecule level. The fluorescence approach described here is conceptually equivalent to RT-QuIC since it relies on ThT staining with an isothermal amplification step.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Tr ials are ongoing to transpose these techniques to clinical set-up. [16] However, these techniques are time consuming (upwards of 50-60 hours), rely on repeated sonication and/or heating steps,all of which can impede the reproducibility of these assays.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PMCA and RT‐QuIC have the ability of detecting αSyn aggregates in biological samples (brain homogenate and cerebral spinal fluid (CSF) with high (>90 %) selectivity and specificity [15] . Trials are ongoing to transpose these techniques to clinical set‐up [16] . However, these techniques are time consuming (upwards of 50–60 hours), rely on repeated sonication and/or heating steps, all of which can impede the reproducibility of these assays.…”
Section: Introductionmentioning
confidence: 99%
“…New strategies to understand and diagnose these proteinopathies are urgently needed as the global burden of cureless dementia is expected to increase by 60% to 75 million people by 2030. 4,5 Whilst the self-assembly of structurally abnormal proteins into so-called ''fibrils'' was initially described in the prion field (the protein implicated in Creutzfeldt-Jakob disease), amyloid proteins involved in other neurodegenerative proteinopathies have been shown to share this property. In particular, the seeding ability of the pathological isoform (templating interaction with its native isoform) is a crucial step into the formation of amyloid fibrils.…”
mentioning
confidence: 99%
“…6 It was shown that RT-QuIC assay is a cutting-edge tool to improve the early diagnosis of human prion diseases and this powerful technique is being extended to other proteinopathies. 4 Indeed, RT-QuIC amplifies in vitro minimal quantities of pathologic isoforms of the protein in biologic samples leading to its detectability. To this end, a recombinant protein is used as a substrate, and Thioflavin-T (ThT) is used as fluorescent reporter to monitor the aggregation phase in real-time while intermittent shaking is performed to foster conversion (see Fig.…”
mentioning
confidence: 99%